Lack of Therapeutic Efficacy of an Anti-α(4)β(7) Antibody in SIVmac251-Infected Rhesus Macaques - Abbink, Peter (Science, 2019)
Sustained virologic control of human immunodeficiency virus type 1 (HIV-1) infection following discontinuation of antiretroviral therapy (ART) is a major goal of the HIV-1 cure field. A recent study reported that anti-α(4)β(7) antibody administration induced durable virologic control following ART discontinuation in 100% of rhesus macaques infected with an attenuated strain of simian immunodeficiency virus (SIV) containing a stop codon in nef. We performed similar studies in 50 rhesus macaques infected with wildtype, pathogenic SIVmac251. In animals that initiated ART during either acute or chronic infection, anti-α(4)β(7) antibody infusion had no detectable effect on the viral reservoir or viral rebound following ART discontinuation. These data demonstrate that anti-α(4)β(7) antibody administration did not provide therapeutic efficacy in the model of pathogenic SIVmac251 infection of rhesus macaques.